Digital Storytelling as a Reflective Tool in Occupational Therapy Curriculum - Amshuda Sonday (Occupational Therapy International)
With a shift in moving towards the 4th industrial revolution, digital storytelling has been identified as a novel way of facilitating teaching and learning. This paper will be aimed at offering an understanding of the experience and perspective of occupational therapy students in using digital storytelling as a reflective tool as an assignment as part of their undergraduate and masters occupational therapy curriculum at a university in South Africa. A descriptive qualitative study was undertaken, and five participants were purposively recruited. Individual semistructured interviews were conducted as well as a focus group with participants. An inductive analysis revealed two themes: Reflections on relevance within the occupational therapy curriculum and Is technology the new direction? The findings conclude that digital storytelling as a medium to showcase reflections on identifying formation was an innovative and novel way of documenting the reflective experiences of occupational therapy students.